Description of Pharmacist Communication In Self-Medication - Riri Amanda Fitriana; Ayu Dwi Utami; Elza Rachman Panca Priyanda; Oktri Lestari; Futri handayani (International Journal of Social Service and Research, 2021)
Self-medication is a process carried out by a person in an effort to treat himself without the help of health workers. However, self-medication that occurs at the pharmacy will be directly guided by a pharmacist. For this reason, what a pharmacist needs to have is the ability to communicate with patients, both verbal communication and nonverbal communication. This study looks at how the preparation of prospective pharmacists in providing information to patients through verbal communication and creating a calm atmosphere through nonverbal communication.